Investigação da ação docente em práticas sociais de leitura de lendas indígenas amazônicas para a formação de alunos de EJA como leitores - Macedo, Lílian Polo de Queiroz (2011)
In general terms, this research aims at investigating my pedagogical practice in a social reading event of Indigenous tales from the Amazon region, as a means to contributing to the education of students as readers, and as a means to honoring the Indigenous culture in the classroom (Mello, 2008, Santilli, 2000, Coelho, 2003). This research is developed within the area of Applied Linguistics, and, by using the research technique and literacy practice of Group Think Aloud (Zanotto,1997, 2000), it investigates two experiences of Amazon tale readings. The investigation was carried out as critical action research (Kincheloe,1997), by means qualitative research of the interpretive type (Chizzotti,2006, Bortoni-Ricardo,2008, Moita Lopes,1996). My own practice as teacher of reading, mediating discussions on the subject of the texts that generate debates about the Indigenous people and their culture - in experiences of the Group Think Aloud (Zanotto,1995,1998) was the focus of investigation. The Group Think Aloud was proposed and has been investigated by GEIM (Study Group of Indeterminacy and Metaphor). The current research was carried out with 22 students in a classroom of EJA (Adult and Youth Education) in a State School in the southern region of Sao Paulo. Data generated by means of Group Think Aloud (Zanotto,1997,2000), semi-standardized interviews (André and Ludke, 2004; Flick, 2009) and retrospective questionnaire (Queiroz,2009) unveiled the following results: 1) Group Think Aloud is an important ally in the education of readers, building their argumentative ability; and in the collaborative construction of meanings of a text; 2) There were changes in my practice since I began to value my students opinions, to give them voice and to see questions as powerful tools in the process of knowledge construction; 3) The Amazon Indigenous tales are effective texts to discuss the Indigenous peoples and their cultures, making room for cultural pluralism in the classroom; 4) In every discussion about the tales, students despite not knowing the Indigenous cultures well showed great interest, respect and admiration for the Indigenous citizen